ANALISIS PERBEDAAN BIAYA TRANSAKSI DALAM ADMINISTRASI PAJAK SISTEM SELF ASSESSMENT PADA PERUSAHAAN SKALA BESAR DAN SKALA KECIL PADA KPP PRATAMA BANDUNG CICADAS - Octavia, Annisa Mulia (2013)
The research is aimed to examine the differences on transactional cost in relation to big and small company. The self assessment system was taken as the primary mean to analyze the issue. The research was taken at KPP Pratama Bandung Cicadas. Single Variable was used in this research which was transactional cost. The through transactional cost and opportunity cost of time was the major concern on the variable. Questionnaire was collected as the main data used in this research. In line with the used of questionnaire as the major data, descriptive analysis was taken in order to find out the differences of the transactional cost between major and minor company. The data result be evidence for Rp. 23.425.000.00 for the tax the opportunity cost of time were Rp. 17.022.366,00 were paid by the minor company. Different with minor company, the data proved that the major company had Rp. 71.750.000,00 and the total of the opportunity cost of time were Rp. 27.296.784,00. In sum, From the entire transactional cost illustrated that the tax cost had the differences almost in any part of some points, such as transportation cost, tax consultation cost, document preparation, requirement learning time, and time to filled SPT. However, the mastering copying of the document and the time of transportation became the similar factor which is showed by the data. Keyword: Transactional Differences Cost, Tax Administration, and Self Assessment System